2006
DOI: 10.1021/ma060451p
|View full text |Cite
|
Sign up to set email alerts
|

Precise Tuning of Micelle, Core, and Shell Size by the Composition of Amphiphilic Block Copolymers Derived from ROMP Investigated by DLS and SAXS

Abstract: Self-assembly of well-defined block copolymers in solution has gained attention not only for its scientific value but also for its potential application in nanotechnology. In this study, we present a comprehensive series of synthesized block copolymers that allows conclusions to be drawn how to design micelles by ROMP with defined core−shell geometry and controlled size. We used a general route for the preparation of well-defined block copolymers by ring opening metathesis polymerization (ROMP) with “Grubbs fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(81 citation statements)
references
References 59 publications
3
77
0
1
Order By: Relevance
“…The data represent the actual values correctly only if micelle formation does not occur. 6,16 For example, the most hydrophobic polymer, 4a, was dissolved in DMFd 7 and the 1 H NMR spectrum showed that the integration value of the isopentyl methyl protons were too low, which are caged in the core of the micelle. However, using CDCl 3 or CD 2 Cl 2 the methyl protons appeared in the 1 H NMR spectrum.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The data represent the actual values correctly only if micelle formation does not occur. 6,16 For example, the most hydrophobic polymer, 4a, was dissolved in DMFd 7 and the 1 H NMR spectrum showed that the integration value of the isopentyl methyl protons were too low, which are caged in the core of the micelle. However, using CDCl 3 or CD 2 Cl 2 the methyl protons appeared in the 1 H NMR spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…3 Ring-opening metathesis polymerization (ROMP) is a versatile technique for the preparation of well-defined block copolymers with narrow distribution of molecular weights. Several amphiphilic block copolymers obtained by the ROMP pathway have been investigated in the literature and were shown to form micelles and nanoparticles, [4][5][6][7][8][9][10][11][12][13][14] and used as drug delivery materials. [15][16][17] Phosphorus-containing polymers have broad application areas; besides their flameretardant properties, 18 they are also used in biomaterials for their adhesive properties to metals, bone, and dentin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A modified literature synthesis [10] was adopted. Synthesis of exo-N-(4,4,5,5,6,6,7,7,7-nonafluoroheptyl)-10-oxa-4-azatricyclodec-8-ene-3,5-dione (monomer D) was done according to the procedure given in reference.…”
Section: Experimental Part Materialsmentioning
confidence: 99%
“…In this study, ring opening metathesis polymerization (ROMP) was employed as a new route for the synthesis of amphiphilic peroxalate copolymers. A ROMP-based synthetic strategy was chosen because ROMP is an effi cient and powerful method to synthesize amphiphilic copolymers which have a well-defi ned structure (Stubenrauch et al 2006;Feng et al 2002). In addition, peroxalate esters which are unstable in the presence of nucleophiles and water can tolerate ROMP reaction conditions (Scheme 1).…”
Section: Synthesis Of Amphiphilic Polynorbornene Copolymersmentioning
confidence: 99%